THE EFFECT OF BLENDED LEARNING MODEL ON STUDENTS’ ACHIEVEMENT IN READING CLASS - Maysarah Maysarah; Sri Wahyuni (LLDIKTI Wilayah X, 2021)
Reading is a skill that is not easy for the student to understand in learning English. However, English teacher at that school still used the monotonous learning model in teaching reading. Hence, this study aimed to find empirical evidence whether teaching using a blended learning model was effective or not on students' reading comprehension of narrative text. This study used a quantitative method and quasiexperiment design. The experimental class and control class were the sample of this study. X DPIB 1 as experimental class consisted of 30 students and X DPIB 2 as controlled class consisted. To take the sample, the researchers used purposive sampling. Students in the experimental class were taught using the blended learning model. In contrast, the controlled class did not use the blended learning model. Theinstrument was a test, and it was divided into pre-test and post-test. The data among pre-test, post-test and gained score were analyzed by using t-test. The pre-test result showed that there were no significant differences between both classes. Then post-test showed that p=0,101 and was greater than α=0.05, and it meant no significant differences in both classes. Furthermore, gained score result showed that p= 0,466 and it also greater than α=0.05. Moreover, based on manual calculation the t0 (tvalue) = 0,762 and tt (ttable) = 1,672, it meant that t0 (tvalue) < tt (ttable) (0,762 < 1,672). Based on the calculation of the t-test, it was proved that the null hypothesis (H0) was accepted. It means that there was a significant effect onstudents reading comprehension who were taught with the blended learning model.